Phase II study of ketogenic diets in relapsing multiple sclerosis: safety, tolerability and potential clinical benefits. Issue 6 (13th April 2022) - Brenton, J Nicholas; Lehner-Gulotta, Diana; Woolbright, Emma; Banwell, Brenda; Bergqvist, A G Christina; Chen, Shanshan; Coleman, Rachael; Conaway, Mark; Goldman, Myla D
Abstract : Background: Dietary changes impact human physiology and immune function and have potential as therapeutic strategies. Objective: Assess the tolerability of a ketogenic diet (KD) in patients with relapsing multiple sclerosis (MS) and define the impact on laboratory and clinical outcome metrics. Methods: Sixty-five subjects with relapsing MS enrolled into a 6-month prospective, intention-to-treat KD intervention. Adherence was monitored with daily urine ketone testing. At baseline, fatigue, depression and quality of life (QoL) scores were obtained in addition to fasting adipokines and MS-related clinical outcome metrics. Baseline metrics were repeated at 3 and/or 6 months on-diet. Results: Eighty-three percent of participants adhered to the KD for the study duration. Subjects exhibited significant reductions in fat mass and showed a nearly 50% decline in self-reported fatigue and depression scores. MS QoL physical health (67±16 vs 79±12, p<0.001) and mental health (71±17 vs 82±11, p<0.001) composite scores increased on-diet. Significant improvements were noted in Expanded Disability Status Scale scores (2.3±0.9 vs 1.9±1.1, p<0.001), 6-minute walk (1631±302 vs 1733±330 ft, p<0.001) and Nine-Hole Peg Test (21.5±3.6 vs 20.3±3.7 s, p<0.001). Serum leptin was lower (25.5±15.7 vs 14.0±11.7 ng/mL, p<0.001) and adiponectin was higher (11.4±7.8 vs 13.5±8.4 µg/mL, p=0.002) on the KD. Conclusion: KDs are safe and tolerable over a 6-month study period and yield improvements in body composition, fatigue, depression, QoL, neurological disability and adipose-related inflammation in persons living with relapsing MS. Trial registration information: Registered on ClinicalTrials.gov under registration number NCT03718247, posted on 24 October 2018. First patient enrolment date: 1 November 2018. Link: https://clinicaltrials.gov/ct2/show/NCT03718247?term=NCT03718247&draw=2&rank=1 .